KORELASI ASPEK KESEHATAN MENTAL TERHADAP MATERNAL FUNCTIONING PADA IBU POSTPARTUM - Fatimah, Siti; Witari, Ni Nyoman Deni; Werdini, Yoessy Etna; Sulastina, Elisabet (Ensiklopedia of Journal, 2025)
Pregnancy and childbirth are complex events that have a significant impact on a woman's condition. After giving birth, many mothers are more vulnerable to emotional disturbances. The purpose of this study was to determine the correlation between mental health aspects and maternal functioning in postpartum mothers. A cross-sectional study design was used in this study. The study was conducted in two hospitals in Makassar. The research was conducted in August 2024. The population consisted of hospitalized postpartum mothers. The sample consisted of 100 respondents. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between anxiety (p value: 0.03) and maternal functioning in postpartum mothers. It is recommended that mothers improve their personalities in a more positive direction, such as thinking positively, not being easily anxious, not being emotional, and building high self-confidence. In addition, mothers should be more open to their partners, families, and others by sharing their complaints or difficulties experienced during the postpartum period. Keywords: Anxiety, maternal functioning, postpartum